LONG-TERM SAFETY AND EFFICACY OF TOCILIZUMAB IN PATIENTS WITH EARLY RHEUMATOID ARTHRITIS OF MODERATE OR HIGH ACTIVITY (RESULTS OF PHASE III MULTICENTER EXTENSION CLINICAL STUDY ML28124) - E. L. Nasonov; M. L. Stanislav; V. I. Mazurov; T. M. Chernykh; V. N. Sorotskaya; T. S. Salnikova; R. S. Saikovsky; O. V. Reshet’ko; T. A. Popova; E. I. Shmidt; V. P. Tyurin; N. P. Shilkina; et al. (Научно-практическая ревматология, 2018)
Objective: to assess the long-term safety and efficiency of tocilizumab (TCZ) therapy in patients with early rheumatoid arthritis (RA) of moderate and high activity, who have completed the basic WA19926 study, as well as the rate of sustained drug-free remission.Subjects and methods. A long-term open-label multicenter Phase III extension study (ML28124) was conducted using a group of 49 patients (36 (73.5%) women and 13 (26.5%) men; mean age 53.3±10.8 years) with early RA of moderate and high activity. All the patients received an intravenous infusion of TCZ 8 mg/kg every 4 weeks for 104 weeks (a total of 27 infusions). The safety assessment criteria were the rate and severity of all adverse events (AE), serious AE (SAE), and AE of particular interest; the rate of AE causing drug dosage changes or withdrawal from the study; the frequency of clinically significant laboratory abnormalities. The analysis of efficiency (secondary end points) included changes of DAS8, which was calculated using erythrocyte sedimentation rate (ESR) (DAS28-ESR) and SDAI, the of tender joint count (TJC) and swollen joint count (SJC); the number of patients who had achieved drug-free remission; and the time to a RA exacerbation in patients who had achieved non-drug remission.Results and discussion. The total rate of AE was found to be 69.4%; that of SAE was 10.2%; SAE were 6.9% of the the total number of AE; AE of particular interest were 17.2% of the total number of AE. More than one-third (35.6%) of the AE caused drug dose changes or therapy discontinuation or complete cessation. The laboratory clinically significant abnormalities included those in complete blood cell counts (blood alanine aminotransferase, aspartate aminotransferase, total and direct bilirubin, creatinine, and glucose). The evaluation efficiency analysis showed that the main disease activity measures (DAS28-ESR, SDAI, SJC, and TJC) decreased at 104-week follow-up versus at baseline. The rate of drug-free remission was 71.4%; that of recurrence was 40.0% (the median time to recurrence was 23 weeks). The findings suggest that the safety profile of TCZ is acceptable in the long-term treatment of early RA and correspond to earlier results.